Lyophilized B. subtilis ZB183 Spores: 90-Day Repeat Dose Oral (Gavage) Toxicity Study in Wistar Rats - B. Appala Naidu; Kamala Kannan; D. P. Santhosh Kumar; John W. K. Oliver; Zachary D. Abbott (Journal of Toxicology)
A 90-day repeated-dose oral toxicological evaluation was conducted according to GLP and OECD guidelines on lyophilized spores of the novel genetically modified strain B. subtilis ZB183. Lyophilized spores at doses of 109, 1010, and 1011 CFU/kg body weight/day were administered by oral gavage to Wistar rats for a period of 90 consecutive days. B. subtilis ZB183 had no effects on clinical signs, mortality, ophthalmological examinations, functional observational battery, body weights, body weight gains and food consumption in both sexes. There were no test item-related changes observed in haematology, coagulation, urinalysis, thyroid hormonal analysis, terminal fasting body weights, organ weights, gross pathology and histopathology. A minimal increase in the plasma albumin level was observed at 1010 and 1011 CFU/kg/day doses without an increase in total protein in males or females and was considered a nonadverse effect. The “No Observed Adverse Effect Level (NOAEL)” is defined at the highest dose of 1011 CFU/kg body weight/day for lyophilized B. subtilis ZB183 Spores under the test conditions employed.